Leopold Weiss alias Muhammad Asad: Von Galizien nach Arabien 1900-1927 by Gunther Windhager (Wein, Austria: Bohlau Verlag, 2002. 230 pages.) (American Journal of Islam and Society, 2002)
It is now 10 years that Muhammad Asad, the twentieth-century's most influential European Muslim, left us. But aside from his own biographical writings-the best-seller The Road to Mecca (1954) and his 1988 interview with his old employer, the Franlifitrter (Allgemeine) 'ZeJtung- until recently there was no comprehensive biography of this illustrious man. This lacuna has now been filled -at least up to his official conversion to Islam in Berlin (1926) and Cairo (1927). This covers his quest as a student, film librettist, and journalist "from Galicia [his native Lemberg and Czernovitz] to Arabia," ending with his preparations for ha]. The author is an unassuming but enthusiastic research assistant for ethnology at Vienna's Austrian Academy of Sciences. Working like a detective and a good prosecutor (never taking a confession at face value), he has written what promises to become the definite biography of the early Leopold Weiss. His pioneering book is welcome for its set of rare (and mostly unpublished) photographs. Of these, a 1932 portrait makes the front cover hauntingly compelling by showing a Ghandi-like Asad with a shaven head and penetrating yet sensitive black eyes. Even better, it includes a three-page chronology, a complete list of his publications that tracks 45 German newspaper articles, and a three-page list of publications on Asad. And yet, despite its being so uncompromisingly academic, his text reads like a novel. It is no surprise that the author discovered that some of The Road to Mecca is elegantly fictitious and, according to Pola Hamida Asad, essen tially a "spiritual autobiography." (Did not Johann Wolfgang van Goethe entitle his Fact and Fiction?) Thus it is now established that his first wife, Elsa Schiemann (nee Sprecht) was not 15 but 22 years older than him, that her little son accompanied them on both "Oriental Journeys" (1922-23 and 1924-26), and that Zayd (their Arab companion) was a literary invention. Windhager reveals other more important facts: details about his mother's Feigenbawn family; the fate of his father, stepmother, and siblings (Dr. med. Heinrich Weiss and Dr.jur. Rachel Weiss) under Nazism, and Asad's attempts to save them from the concentration camps; his days at Vienna University, where he not only studied the history of art and philosophy but ...